Age-specific seroprevalence of human polyomavirus 12 and Saint Louis and New Jersey polyomaviruses - Gaboriaud, Pauline (Emerg Microbes Infect, 2018)
The presence of specific antibodies against human polyomavirus 12, Saint Louis polyomavirus and New Jersey polyomavirus was investigated by using virus-like particle-based ELISAs with serum samples from 706 Italians aged 1- to 100-years-old. The findings indicate that these polyomaviruses circulate widely in humans, with peak seroprevalence, observed at adulthood, of 97.3%, 93.3%, 57.5%, for human polyomavirus 12, Saint Louis polyomavirus and New Jersey polyomavirus, respectively.